Investigation of the Mineral Content of Laterite Soil and Nickel Ore in the Nickel Mining Area of PT Vendoura Inti Perkasa, Bahodopi District, Morowali Regency - W. S. Nurjannah; L. Agusu; R. Eso (International Journal of Acta Material, 2026)
This study aims to identify and analyze the mineral composition of lateritic soils in a nickel mining area. Sampling was conducted vertically at 50 cm intervals, reaching 700 cm and covering four laterite soil layers: topsoil, limonite, saprolite, and bedrock. The materials were dried, crushed, and sieved using a 200-mesh screen. The samples were then analyzed for elemental content using X-ray fluorescence (XRF) and for mineral composition using X-ray diffraction (XRD). The XRF results show that SiO₂ and MgO are more concentrated in the bedrock and saprolite layers, while Fe and Al₂O₃ are more dominant in the topsoil and limonite layers. The presence of goethite (hydroxide) in the limonite layer at both points indicates hydrated iron oxides typical of lateritic profiles. Hematite (oxide) was found in the limonite rock at Point 1, while antigorite and chrysotile (silicates) were found at Point 2. In the saprolite layer, hematite was identified at Point 1 and goethite at Point 2. In the bedrock, lizardite was found at Point 1 and olivine at Point 2, suggesting a parent material of weathered ultramafic or metamorphic origin. The presence of goethite confirms typical characteristics of lateritic soils rich in hydrated iron oxides.